Aging promotes a different phosphatidic acid utilization in cytosolic and microsomal fractions from brain and liver - Pasquaré, Susana Juana (2001)
Among the morphological and biochemical changes taking place in the membranes of aged tissues, we reported in previous studies on alterations in phospholipid synthesis and phospholipid-specific fatty acid composition. Phosphatidic acid (PA) and diacylglycerol (DAG) are central intermediates in phosphoglyceride and neutral lipid biosynthetic pathways and have also recently been implicated in signal transduction. The present paper shows the effect of aging on phosphatidate phosphohydrolase (PAPase) activiy, which operates on phosphatidic acid to synthesize diacylglycerol. Two forms of mammalian PAPase can be indentified on the basis of subcellular localization and enzyme properties, one involved predominantly in lipid synthesis (PAP 1) and the other in signal transduction (PAP 2). Microsomal and cytosolic fractions of brain and liver from 3.5-month-old (adult) and 28.5-month-old (aged) rats were used. PAPase isoform activities were differentiated on the basis of N-ethylmaleimide (NEM) sensitivity and Mg2+-dependency. Our results demonstrate that aging caused PAP 2 to increase in brain microsomal fractions but did not affect PAP 1, whereas in brain cytosolic fractions, it caused a strong decrease in PAP 1 (57%). The distribution of enzymes between microsomes and cytosol changed in aged rats with respect to adult rats, showing a translocation of PAP 1 from cytosol to microsomes. In addition, an increase in the production of monoacylglycerol (MAG) was observed in microsomes from aged brain. PAP 2 activity in liver microsomal fractions from aged rats showed no changes with respect to adult rats whereas PAP 1 activity increased 228% in microsomal fractions and 76% in cytosolic fractions in this tissue. The distribution of PAP 1 activity between microsomal and cytosolic fractions in liver tissue was also affected in aged rats, indicating a translocation of this form of the enzyme from cytosolic to microsomal fractions. The production of monoacylglycerol in liver microsomes also increased, whereas there was a decrease in MAG formation from cytosolic fraction. The changes observed in the two PAPase forms in brain and liver of aged rats with respect to adult rats suggest that PA is differently utilized by the PAPase isoforms, probably generating aging-related DAGs different to those present in adults and required for specific cellular functions. The changes observed in liver PAP 1 from aged with respect to adult rats suggest that such changes could be related with modifications in lipid homeostasis induced by age-altered hormonal balance. However, PA-modified utilization during aging through PAP 2 activity could be related to alterations in neural signal transduction mechanisms.